Stimulating Financial Planning Behavior Through Frontline Employees: a Triadic Analysis of the Role of Servant Leadership and Customer Stewardship Climate in Islamic Banks in Indonesia - Heni Indah Pratiwi; Galih Fajar Muttaqin; Edward Fazri (Sean Institute, 2025)
Objectives This study aims to investigate the mechanisms through which Frontline Employees (FLEs) in Islamic banks in Indonesia can motivate improved customer financial planning behavior. This study further analyzes how servant leadership and customer stewardship climate strengthen these mechanisms. Design/Methodology or Approach This quantitative study used a triadic approach with data collected from 45 managers, 165 FLEs, and 600 customers from various Islamic banks in Java and Sumatra. Data were analyzed using Structural Equation Modeling (SEM) with bootstrapping techniques to test the mediation and moderation hypotheses. Findings The results prove that FLEs' attention to detail significantly improves customer financial planning behavior through multiple mediation, namely service customization and promotion focus. Another key finding shows that servant leadership and customer stewardship climate positively moderate the relationship between attention to detail and service customization, thereby strengthening the overall indirect effect. Limitations or Implications of the Study The geographic scope and sector (Islamic) specificity are the main limitations. The research implications emphasize the importance of recruiting and training FLEs who are detail-oriented and empathetic, as well as building an organizational culture supported by servant leadership. Originality or Value: This research is one of the first to integrate Regulatory Focus Theory and Conservation of Resources Theory in the context of Islamic financial services in Indonesia. Using a triadic approach, this study provides empirical evidence on the synergy between individuals (FLEs), leadership, and organizational climate in achieving transformative outcomes for customers.